2023
DOI: 10.3389/fvets.2022.1073659
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation with dandelion tannins or soybean isoflavones on growth performance, antioxidant function, intestinal morphology, and microbiota composition in Wenchang chickens

Abstract: Many benefits have been found in supplementing tannins or soybean isoflavones to poultry, including increased body weight gain, antioxidant activity, and better intestinal morphology. However, few studies tested the influence of dandelion tannins or soybean isoflavones supplementation on Wenchang chickens. This study investigates the effects of dietary supplementation with dandelion tannins or soybean isoflavones on the growth performance, antioxidant function, and intestinal health of female Wenchang chickens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 75 publications
1
6
0
Order By: Relevance
“…Other studies have also reported that dandelion supplementation could improve growth, immune response, antioxidant activity, and nutritional capacity in fish (Du et al., 2022 ; Yu et al., 2022 ; Zhao et al., 2022 ) and enhance lactation, antioxidant activity, and serum carbohydrate and amino acid metabolism in cows (Li, Mei, et al., 2023 ). Similar effects on chickens upon supplementation with dandelion tannins have also been reported (Li, Sun, et al., 2023 ).…”
Section: Introductionsupporting
confidence: 78%
“…Other studies have also reported that dandelion supplementation could improve growth, immune response, antioxidant activity, and nutritional capacity in fish (Du et al., 2022 ; Yu et al., 2022 ; Zhao et al., 2022 ) and enhance lactation, antioxidant activity, and serum carbohydrate and amino acid metabolism in cows (Li, Mei, et al., 2023 ). Similar effects on chickens upon supplementation with dandelion tannins have also been reported (Li, Sun, et al., 2023 ).…”
Section: Introductionsupporting
confidence: 78%
“…The serum biochemical indexes can reflect the metabolic state of animal tissues and organs to a certain extent. [ 32 ] The higher contents of TP and ALB were in favor of the uptake of amino acids in the body, which are functionally active in metabolism and protein synthesis. Amino acid is the precursor of milk protein synthesis in milk.…”
Section: Discussionmentioning
confidence: 99%
“…Tannins significantly upregulate ZO-1 levels to protect against jejunal barrier damage. Research has shown that dietary TA supplementation can increase the mRNA levels of ZO-1, claudin-1, claudin-2, and occludin to mitigate intestinal barrier damage [ 53 , 54 ]. In line with prior research, we found that dietary supplementation with 1000 mg/kg TA raised the mRNA levels of claudin-2 and occludin, which suggested that dietary supplementation with TA is beneficial in ameliorating jejunal barrier damage in CCP-challenged broilers.…”
Section: Discussionmentioning
confidence: 99%